A comparison study of cleanup techniques for oil spill treatment using magnetic nanomaterials. (15th July 2019) - Cardona, D.S.; Debs, K.B.; Lemos, S.G.; Vitale, G.; Nassar, N.N.; Carrilho, E.N.V.M.; Semensatto, D.; Labuto, G.
Abstract: Magnetic nanoparticles have been successfully used to recovery oil from oil spilled on water. Two different methods, floating and vortex, were employed to promote the interaction of four oil samples with different API (e.g., 10, 20, 28 and 45) spilled on seawater and deionized water with three magnetic materials, namely: magnetite nanoparticles (N); magnetic nanocomposites of yeast biomass provided by ethanol industry (Y); and magnetic nanocomposites of cork powder (C). The magnetic nanomaterials exposed to oil on water were taking out by a neodymium magnet, and the oil recoveries were determined by gravimetric analysis before and after lyophilization. The lyophilization was determinant to guarantee the accuracy of the experiments, and without this step, the masses of oil recovered would be overestimated due to the drag of water during the oil and magnetic material removal process. Three main factors, API, contact method and magnetic material, and two interactions (i.e., API × contact method, and contact method × magnetic material) presented a statistically significant effect on oil recovery. It was observed that oil recovery increases as API decreases, and it was possible to establish a model to predict the amount of recovered oil according to this effect. Higher oil recoveries were also obtained by magnetic nanocomposites of yeast biomass (Y), regardless of the contact method and type of water, recoveries of 23% and 100% for 45 and 10 API, respectively, employing around 20 mg of Y on 300 mg of spilled oil. These percentages correspond to 0.29 ± 0.01 kg/kg and 15.98 kg/kg of recovering oil by the magnetic procedure. The increase of mass of magnetic material improved the recovery of oils with higher APIs. The reusability of the spent materials presents potential for its application in oil spill cleaning technologies. Highlights: It is possible to predict the amount of recovered oil according to the API. The oil recovery increases as API decreases. The API, contact method and magnetic material were the significant on oil recovery. Interactions of contact method with API and magnetic material are also significant. Lyophilization is crucial to guarantee the accuracy of oil recovering amounts.